ANALISIS KUALITAS AIR BERSIH MENGGUNAKAN INDEKS PENCEMARAN DI RUMAH SAKIT UMUM DAERAH MANOKWARI - Syafrudin Raharjo; Bulfrit Berstian Rajagukguk; Sadida Anindya Bahtiar; Jhohan (Nusantara Hasana Journal, 2026)
Clean water is a primary need that is essential and fundamental to the survival and health of hospitals. This study aims to evaluate the water quality of Manokwari Regency Hospital using the Pollution Index method to identify the main sources of contamination and their implications. The tested samples were then compared with the quality standards stipulated in Minister of Health Regulation Republic of Indonesia No. 32 of 2017. The pollution index analysis for the physical and chemical parameters was 0.618. Thus, the physical and chemical parameters of the water in Manokwari Regency Hospital meet the standards for hygiene and sanitation needs. Although the physical and chemical parameters met the specified quality standards, the results of the biological parameter tests exceeded the specified quality standards. The total coliform content was below the specified quality standards. However, the water from Manokwari Regional Hospital was contaminated with E. coli bacteria, with three colonies of E. coli bacteria in 100 ml of sample water. This is suspected to be due to the water source being contaminated by soil from fecal waste. Therefore, selecting a clean water source and managing it for sanitation and hygiene needs is necessary.